Branching fractions and CP-violating asymmetries in radiative B decays to eta K gamma - Aubert, B; Bona, M; Karyotakis, Y; Lees, J; Poireau, V; Prencipe, E; Prudent, X; Tisserand, V; Tico, J; Grauges, E; Eigen, G; Stugu, B; et al. (2009)
We present measurements of the CP-violation parameters S and C for the radiative decay B0→ηKS0γ; for B→ηKγ we also measure the branching fractions and for B+→ηK+γ the time-integrated charge asymmetry Ach. The data, collected with the BABAR detector at the Stanford Linear Accelerator Center, represent 465×106 BB̄ pairs produced in e+e- annihilation. The results are S=-0.18-0.46+0.49±0.12, C=-0.32-0.39+0.40±0.07, B(B0→ηK0γ)=(7.1-2.0+2.1±0.4)×10-6, B(B+→ηK+γ)=(7.7±1.0±0.4)×10-6, and Ach=(-9.0-9.8+10.4±1.4)×10-2. The first error quoted is statistical and the second systematic. © 2009 The American Physical Society.